Pandemic Shocks and Household Spending. (2nd December 2021) - Finck, David; Tillmann, Peter
Abstract: We study the response of daily household spending to the surprise number of fatalities of the COVID‐19 pandemic, which we label as a pandemic shock. Based on daily forecasts of the number of fatalities, we construct the surprise component as the difference between the actual and the expected number of deaths. We allow for state‐dependent effects of the shock depending on the position on the curve of infections. Spending falls after the shock and is particularly sensitive to the shock when the number of new infections is strongly increasing. If the number of infections grows moderately, the drop in spending is smaller. We also estimate the effect of the shock across income quartiles. In each state, low‐income households exhibit a significantly larger drop in consumption than high‐income households. Thus, consumption inequality increases after a pandemic shock. Our results hold for the US economy and the key US states. The findings remain unchanged if we choose alternative state‐variables to separate regimes.